KOSAKATA DALAM TRADISI BETANGAS MASYARAKAT MELAYU DESA SUNGAI RAYA KABUPATEN BENGKAYANG: KAJIAN SEMANTIK - Mia Audina; Ahadi Sulissusiawan; Ahmad Rabi’ul Muzammil (Universitas Tanjungpura, 2021)
AbtractThis Research is motivated by an interest in the existing culture of the Sungai Raya Malay community so that it can be developed in a study. The problem discussed in this study is the vocabulary contained in the betangas tradition of the Sungai Raya Malay community. The purpose of this study was to analyze the lexical meaning, cultural meaning, and fuction of the vocabulary contained in the term in the betangas tradition. This research uses descriptive method in the form of qualitative. The data sources in this study are native speakers of the Sambas Malay Language who understand the implementation of the betangas tradition. The data in this study are vocabulary in betangas tradition related to the presentation of the term of the betangas tradition lexical meaning and forms of terminology, cultural meaning, and vocabulary fuctions founds in the malay community in Sungai Raya. The technique used in data collection is using direct, interview and indirect technique, direct observation and recording. Furthermore, the tools for data collection were using a recording device, a list of question and writing instrumentsto record the data. Based on the results of the study, obtained 59 terms in the betangas tradition. The form of term found in the betangas tradition is monomorphemic form of 30 data which is divided into 23 data noun, 4 data adjectives, and 3 data verb. Then in polymorphemic form there are 8 data which are divided into 6 data prefix affxation anda 2 data suffix affixation. Finally, the phrase from caontains 21 data. Furthermore, based on the type of meaning contained in the betangas tradition, 9 term have two meanings, namely lexical meaning and ciltural meaning, while for the other 50 terms only have lexical meaning. As having varius fuctions in the vocabulary of the betangas tradition.Keyword: Betangas Tradisition In Malay Community Sungai Raya Village, Meaning, Semantic